#1**+2 **

There may be a better way but I started by expanding it all out and simplify

Taking it to one side and put equal to 0

After you do that and present your answer here I will help you more.

Melody Jan 5, 2020

#2**+1 **

n^{3}= n^{3}-1+n^{3}-8+n^{3}-27

n^{3}=n^{3}+n^{3}+n^{3}-1-8-27

n^{3}=3n^{3}-9-27

n^{3}=3n^{3}-18

-n^{3}+n^{3}=-18/3

6 (ans)

sadaatkhan Jan 5, 2020

#4**0 **

Expanding a little bit on Melody's answer...

You expand and get \(n^3 = (n^3-3n^2-3n+1)+(n^3-6n^2+12n+8)+(n^3-9n^2+27n-27)\).

Solve from here.

CoolStuffYT Jan 5, 2020